Impact of Containerization Development in the Port Of Rijeka on the Rijeka Traffic Route - Hlača, Bojan; Mezak, Vlado; Papeš, Sniježana (Promet - Traffic&Transportation, 2008)
The Container terminal of the Port of Rijeka is highlypromising due to the high rising trend of container traffic. Thecontainer terminal competitiveness of the Ports of Rijeka, Triesteand Koper shall be compared by competitiveness matrixdemonstrating the justifiability of investments in containerizationof the Port of Rijeka. The competitiveness also depends onthe traffic conne.ction between port and hinterland indicatingthe need to modernize traffic routes connecting the port to thetraffic network. Investments in port and traffic infrastructureprove their justification in upgrading a level of container terminalquality and capacity as well as in increasing incomes thatcan be generated by implementing the development plans formodernization of the port, railroad and road infrastructure.